Maintenance of diet participation in individuals with spinal cord injury: effect on mood and neuropathic pain. (December 2018) - Allison, David; Ditor, David
Abstract Study design: One-year follow-up of a randomized clinical trial. Objectives: Examine voluntary dietary compliance 1 year following the cessation of the intervention and the persistence of accrued benefits related to neuropathic pain and mood. Setting: Outpatient rehabilitation program within the Niagara region. Methods: Five individuals (4 female, 1 male; age 50.6 ± 11.8 years) with chronic SCI (C5-L3; ISNCSCI: A–D; 7–40 years post injury) who had previously completed a 3-month anti-inflammatory diet were reassessed after 1 year for measures related to dietary compliance, CES-D scores of depression, and NPQ scores of neuropathic pain. Results: There was a significant reduction in diet compliance at the 1-year follow-up in comparison to the end of the dietary intervention at 3 months (92.6% versus 43.0%, p < 0.01). CES-D scores showed a trend toward an increase from 3 months to follow-up (8.0 versus 21.4, p = .10) whereby follow-up CES-D scores were no longer statistically different from baseline (p = 0.74). Sensory NPQ scores showed no significant change from 3 months to follow-up (25.2 versus 29.1, p = 0.42) and remained significantly lower than baseline (p = 0.02). Affective NPQ scores were significantly increased from 3 months to follow-up (27.7 versus 40.1, p = 0.05). Sensitivity NPQ scores showed no significant change from 3 month to follow-up (28.2 versus 33.5, p = 0.34), but returned to a score that was statistically similar to baseline (p = 0.15). Conclusions: These results emphasize the importance of continued compliance to a diet with anti-inflammatory properties for the purposes of maintaining benefits related to mood and neuropathic pain in individuals with SCI. Sponsorship: This study was supported by the Ontario Neurotrauma Foundation.